RPA-CRISPR/Cas12a-based detection of Pasteurella multocida: establishment and initial application - Yan, Chaoqun; Li, Xiaozhen; Chen, Rulong; Wu, Quanxin; Zhuang, Youquan; Li, Na; Ma, Xuelian; Chu, Yuefeng; Shi, Huijun; Fu, Qiang; Yang, Li (Frontiers in Veterinary Science, 2026)
IntroductionPasteurella multocida (Pm) is a major pathogen that causes respiratory diseases in sheep, leading to high morbidity, high mortality, and significant economic losses. Current diagnostic methods, such as bacterial isolation, ELISA, and PCR, are limited by low throughput, complex procedures, and reliance on specialized equipment, making them unsuitable for field use.MethodsIn this study, we developed a rapid, visual, and sensitive method for detecting Pm by combining recombinase polymerase amplification (RPA) with CRISPR/Cas12a. The PCR method based on kmt1 is the “gold standard” for studying Pm. So this assay targeted the kmt1 gene and was optimized for primer selection, reaction conditions, and crRNA/Cas12a ratios. Specificity verification was conducted through common respiratory pathogens, and sensitivity verification was carried out using plasmid dilution solutions.ResultsThe method showed a detection limit of 5 × 10−1 copies/μL, and the reactions were completed within 30 min. When applied to 102 clinical samples, the RPA-CRISPR/Cas12a assay yielded a positive rate of 40.20% (41/102), which was 4.1 times higher than that of PCR. This assay offers a promising tool for rapid and instrument-free detection of Pm in frontline clinical settings.